Prosty język w komunikacji prawniczej – okiem redaktora językowego - Zandberg-Malec, Justyna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2021)
The article discusses the practical use of plain language rules in editing law-related texts. The author believes that it is possible and worth the effort to write legal texts in accordance with the rules of plain language, i.e. with the expected reader in mind, giving examples of rewritten sentences taken from the articles for an online law portal. The author divides the processes in terms of ‘structural order’ and ‘linguistic order’ and shows that even cosmetic editing in the spirit of plain language, without affecting the text’s structure, improves its intelligibility.